Comportamento verbal: uma análise de pesquisas experimentais desenvolvidas com participantes neurotípicos - Garcia, Aliny Feliciano Soares (2021)
Since the publication of the book Verbal Behavior in 1957, numerous research programs have been conducted on verbal behavior. However, such programs were directed almost exclusively to the study of primary verbal operants, aiming at the development of elementary repertoires for the population with atypical development, especially children diagnosed with Autistic Spectrum Disorder (ASD). This literature review of experimental research aimed to investigate the number of publications, objectives and results from empirical studies with neurotypic participants published in The Analysis of Verbal Behavior. The manual search performed in all volumes of the journal (from 1982 to 2020) resulted in 45 articles that integrated 65 studies. The results show that there are: few studies with this population; focus on investigations on primary verbal operants, with emphasis on the verbal operant of intraverbal; the predominance of adult participants in basic studies; the description of fully effective results in most studies; few generalization measures in applied studies; and the scarcity of studies that investigate other behavioral phenomena (e.g., autoclitics, selfediting), explained in the book Verbal Behavior. New directions in the research field are expected, aiming at consolidating Skinner's proposal for verbal behavior as a possible model for interpreting other phenomena beyond the primary verbal operants